Experimental study of the extraction of chromium (III) from nitrate medium by lauric acid - Guerdouh, Amel; Barkat, Djamel (Metallurgical and Materials Engineering, 2018)
The solvent extraction of chromium (III) with lauric acid (HL) at 25 °C is studied as a function of various parameters: pH of the aqueous phase, the concentration of lauric acid and the nature of the solvent. The solvent effects on the extraction of chromium (III) using polar and nonpolar solvents has been observed. It was shown that extracted species of the [Cr(OH)L2 ·2HL] formula are formed in cyclohexane, dichloromethane, chloroform, and toluene. However, in 1- -octanol or methyl isobutyl ketone, it was found a complex of the type [Cr(OH)L2]. The extraction constants and extraction yield (%E) are also calculated for different solvents. It was found that cyclohexane is the preferred solvent for this extraction system, The maximum extraction yield is accomplished using the cyclohexane as a solvent on 1:1 L/L ratio, and pH value of 4.73.